1978
DOI: 10.1093/nar/5.8.2959
|View full text |Cite
|
Sign up to set email alerts
|

Activation and inactivation of neocarzinostatin-induced cleavage of DNA

Abstract: The possible role of free radicals in the mechanism of neocarzinostatin (NCS) action was studied. While mercaptene markedly stimulate the ability of NCS to degrade DNA, they also rapidly inactivate the antibiotic in a preincubation and at higher concentration inhibit the degradation reaction. The radiation protector S,2-aminoethylisothiuronium bromide-HBr is the most potent compound tested. Scavengers of diffusible OH radicals, O2- or H2O2 do not result in significant inhibition of the oxygen-dependent cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 18 publications
(5 reference statements)
8
64
1
Order By: Relevance
“…Comparison of the biological properties of NCS and macromomycin has been reported (12, 17). The assays for NCS-induced scission of [methyl-3H]thymidine-labeled linear X DNA and supercoiled pMB9 DNA have been described (9,17). DNA synthesis and drug-induced DNA strand scission in HeLa cells were measured as reported (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the biological properties of NCS and macromomycin has been reported (12, 17). The assays for NCS-induced scission of [methyl-3H]thymidine-labeled linear X DNA and supercoiled pMB9 DNA have been described (9,17). DNA synthesis and drug-induced DNA strand scission in HeLa cells were measured as reported (17).…”
mentioning
confidence: 99%
“…NCS introduces single-strand breaks almost exclusively at thymidylate and adenylate residues in DNA in vitro (3)(4)(5) in a reaction greatly stimulated by a sulfhydryl compound (3,(6)(7)(8)(9) and dependent on oxygen (9)(10)(11). Evidence for the existence of an active, labile form of NCS that causes single-strand breaks in linear and supercoiled DNA has been presented (9,12). With the recent demonstration that NCS contains nonprotein, chromophoric material that has UV-visible absorption above 300 nm and fluorescence emission at 420 nm and 490 nm and that can be separated from the protein (13), the question arises as to its possible role in NCS action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The assay for thiol potency as a reducing agent for neocarzinostatin in a cell-free system depends on the fact that, when neocarzinostatin is reduced by thiols in the absence of DNA, reduced neocarzinostatin attacks itself, losing biological activity (9). The decreased activity of the drug is assessed, in turn, by testing the ability of the preincubated neocarzinostatin/thiol mixture to alter neuroblastoma cell morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we also hypothesized that the toxicity of NCS in normal cells was weak because NCS inhibits DNA synthesis in growing cells, such as tumor cells. 44 At a higher dosage, however, V2-05i[IgG]-NCS carries the risk of side effects. With regard to this point, none of the anti-Robo4 ADCs induced a loss of body weight; therefore, we concluded that Robo4 is a potential target for tumor vascular targeting with ADC.…”
Section: Enhanced Antitumor Effect Depends On the Cell-internalizing mentioning
confidence: 99%